Online Gaming and the Social Construction of Virtual Victimization - Downing, Steven (Eludamos: Journal for Computer Game Culture, 2010)
Online computer gaming is becoming an increasingly popular leisure activity as well as a growing context for social networking and social interaction in general. Drawing from a cyber-ethnography conducted in one such online game, I analyze the process by which the notion of victimization is socially constructed within the online gaming community. I contextualize this analysis within the framework of social construction theories, specifically addressing how internal and external norms, beliefs and values influence the assessment of the severity of virtual harm and the subsequent validity of victim claims. The reported findings suggest a distinction between virtual violence and theft within the context of the game; the latter being assessed as more harmful to the cohesiveness of the online community as well as the individual victim. Reasons for this distinction as well as a broader analysis of the interaction between online and offline culture is discussed.